Characterization of lung adenocarcinoma with a cribriform component reveals its association with spread through air spaces and poor outcomes. (August 2019) - Ding, Qifeng; Chen, Donglai; Wang, Xiaofan; Wen, Junmiao; Chen, Chang; Zhang, Yongsheng; Xu, Zhonghua; Chen, Yongbing
Graphical abstract: Highlights: The cribriform component was significantly associated with the presence of STAS. The cribriform component and STAS were significantly associated with poor prognosis. STAS status could provide prognostic information in LUADs with a cribriform component. Abstract: Objective: To further investigate the relationship between the cribriform component and spread through air spaces (STAS), and to unravel the potential pathological mechanism of poor prognoses in lung adenocarcinoma (LUAD) patients with a cribriform component. Methods: We retrospectively reviewed the clinicopathological characteristics of 208 LUADs. The cribriform component was identified by hematoxylin and eosin staining. The identification of STAS referred to our previous study. The relationship between the cribriform component and STAS was determined by using a logistic regression model. The effects of the cribriform component and STAS on prognosis were analyzed using a Cox proportional hazards regression model. Results: LUAD patients with a cribriform component had significantly inferior outcomes and increased risk of both locoregional and distant recurrences when compared with those with no cribriform component ( p  < 0.001). Among 67 patients with a cribriform component presented, 48 (71.6%) cases had STAS. The logistic regression model identified that the cribriform component was an independent risk factor for the presence of STAS ( p  = 0.044). Subgroup analysis showed that Crib+ (cribriform component present)/STAS+ (spread through air spaces positive) patients had significantly inferior outcomes when compared with Crib+/STAS- (spread through air spaces negative) patients ( p  < 0.001). Moreover, the multivariate Cox regression analysis further confirmed that STAS was an independent risk factor for a worsening recurrence-free survival (RFS) ( p  = 0.001) and overall survival (OS) ( p  < 0.001) in LUAD patients with a cribriform component. Conclusions: Our results indicated that STAS was more frequently observed in LUAD patients with a cribriform component. Moreover, STAS could provide helpful prognostic information in patients with stage I-III LUAD with a cribriform component.